An investigation into relationship marketing in South African family businesses - Eboru, Rolland (My University, 2014)
According to the Department of Trade and Industry (DTI) (2004), it is estimated that there is a total of 1.42 million active businesses in South Africa, 84 per cent of which are classified as “family business”. Internationally, family businesses account for 70 per cent of all international businesses and 35 per cent of Fortune 500 companies (Balshaw, 2004). Despite their economic importance, family businesses still find marketing to be a challenge. Relationships are at the heart of family businesses (Petzinger, 1999; Cooper, Upton and Seaman, 2005). This is because the fundamental DNA (Deoxyribonucleic Acid) a family business is based on a symbiotic relationship between the family and the business. Families, by virtue of their DNA, cultivate deep relationships with people, which include customers, suppliers and even competitors. Hence, in a family business context, these values are transferred into the business by the associated family. This relational approach is often utilised in the marketing strategies that they adopt. This study investigates some of the characteristics of relationship marketing that exist in South African family businesses. The results from the family businesses surveyed, indicates that they cultivate deep relationship with customers. This characteristic enables these businesses to be highly proficient at both satisfying and retaining customers. However, despite a culture of customer centricity, further findings indicate that such businesses are less proficient regarding their orientation with competitors, as they are often slow to respond to competition, in the market place. Lastly, the study indicates that family businesses cultivate and maintain a healthy relationship with employees; as such relationships is a prerequisite for customer satisfaction.
Keywords: Family business; Relationship marketing; Market orientation; Customer satisfaction